Empat Plus Satu untuk Swing Trader - Ronny Thomas; Nurlia Nurlia (The Indonesia Capital Market Institute, 2021)
This research focuses on technical analysis, which gives signals to trading stocks when to enter, and when to exit the market, in a transaction in the capital market. The indicators used are RSI, MACD histogram, stochastic, ADX, and + candlesticks. During the Covid 19 pandemic, where prices were moving SIDEWAYS. The concept of